JUNIOR HIGH SCHOOL ENGLISH TEACHERS’ PLANNING ON MERDEKA CURRICULUM - Latifa, Helmia; Ratih, Koesoemo; Maryadi, Maryadi (University of Kuningan, 2024)
The purpose of this study was to determine teachers’ planning for implementing Merdeka curriculum in teaching English. This research is phenomenological research. Researchers used observation, interviews, and documentation to obtain data. The research data are statements from English teachers, principal, and deputy principals in the field of curriculum, pictures from observations, and documentation. The results of this study showed that the teacher made four plannings` for the implementation of Merdeka curriculum. These plannings are assessment, teaching device, flow of learning objectives, and teaching modules. Therefore, these plannings are carried out by the teachers so that the implementation of Merdeka curriculum in learning English is successful. School needs to develop professionalism for teachers to increase understanding of Merdeka curriculum, especially in English language learning